Zooplankton of a large impoundment - Bagha dighi in Rajshahi, Bangladesh - Alom, MN; Zaman, M (University Journal of Zoology, Rajshahi University, 2007)
Key words: Zooplankton; Bagha dighi; Rajshahi; Bangladesh Univ. j. zool. Rajshahi Univ. Vol.23, 2004. pp. 53-60